Understanding the Qur'an as a Cultural Product: A Study of Nasr Hamid Abu Zayd's Thought - Bimba Valid Fathony (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Nasr Hamid Abu Zayd, an intellectual from Egypt, argued that the Quran is a 'cultural product' (muntaj thaqafi). This means that the text of the Quran was formed in reality and culture for more than 20 years. Historically, the text of the Quran does not appear in a vacuum. The text of the Quran contains all the cultural elements from which it was revealed. This study aims to delve deeper into Nasr Hamid Abu Zayd's thoughts regarding the view of